The Effect of Waiting Time on Patient Satisfaction at Sabokingking Health Center Palembang - Desiwantara Desiwantara; Siti Zubaidah; Doris Febriyanti; Atrika Iriani (Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study aims to analyze the effect of service waiting time on patient satisfaction at the Sabokingking Community Health Center in Palembang. Waiting time is an important aspect in assessing the quality of health services because patients not only assess the results of medical procedures but also their experience during the process of receiving services. This study uses a quantitative approach with a survey method. Data were collected through the distribution of Likert-scale questionnaires to 60 patient respondents, then analyzed using the SPSS application. Tests carried out include validity, reliability, normality, heteroscedasticity, multicollinearity, simple regression analysis, t-test, F-test, and coefficient of determination. The results showed that the research instrument was valid and reliable, with a Cronbach's Alpha value of 0.960 for the service waiting time variable and 0.955 for the patient satisfaction variable. The regression results showed a coefficient value of 0.663 with a significance of 0.000, while the R Square value was 0.627. These findings indicate that service waiting time has a positive and significant effect on patient satisfaction by 62.7%, while the rest is influenced by other factors outside the study. Thus, increasing the efficiency of waiting times needs to be a concern in efforts to improve the quality of service at the Sabokingking Palembang Community Health Center.